Supply Chain Operation Model in Digital for Service Management in the Library in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research about supply chain operation model in digital for service management in the library in Thailand is important for the effectiveness of the model as well as the application in actual work settings. Literature on supply chain management and digital in Thailand was reviewed. The research aim were to design supply chain operation model in digital for service management in the library in Thailand and to evaluate supply chain operation model in digital for service management in the library in Thailand. A sample groups consisted of ten experts in the field of digital technology and Information Science and Library Science. Data analysis was the average mean and standard deviation. The research was found that supply chain operation model in digital for service management in the library in Thailand consists of six components: namely main components, Publishers, Libraries, Users of the library, Satisfaction, Feedback. The results from ten experts agreement supply chain operation model in digital for service management in the library in Thailand. The model aims to support sustainable digital system development.